PENGARUH TIPE ENDORSER DAN KECOCOKAN ENDORSER-MERK PADA SIKAP TERHADAP ENDORSER, MERK, IKLAN DAN NIAT BELI FASHION HIJAB MUSLIMAH DI INSTAGRAM - Susilowati, Fitriah Dwi; Futuwwah, Ali Imaduddin (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to examine the relationship between endorser type and endorser-brand suitability on attitudes towards endorsers, attitudes towards brands, attitudes towards advertising, and purchase intentions. Design/methodology/approach- Data were collected through an online questionnaire of 180 participants. The data analysis techniques used were MANOVA and SEM (PLS). Findings- There are significant differences in attitudes towards endorsers, brands, and advertisements from differences in endorser-brand suitability. There was no significant effect of using endorsers with celebrity types and Instagram influencers on attitudes towards endorsers, brands, and advertisements. Attitudes towards endorsers and brands have a positive effect on purchase intentions. Implication- Companies should pay attention and conduct in-depth research on endorsers that match the brand image. B2C marketers must identify and engage professionally with celebrities or influencers who are popular with consumers. Keywords: Endorser, endorser-brand compatibility,